rmpM gene as a genetic marker for human bacterial meningitis - Dash, S. K.; Sharma, M.; Khare, S.; Kumar, A. (Cellular and Molecular Biology, 2012)
Meningitis is a bacterial, viral or fungal infection of the protective membrane meninges covering the brain and spinal cord. Viral and other forms of meningitis are mild and get cured within one or two week without any treatment. Whereas, bacterial meningitis can prove lethal if not being diagnosed or treated in time. Meningitis is a contagious infection and can spread from one person to another through coughing, sneezing or close contact. Usually the disease is diagnosed from cerebrospinal fluid (CSF) of the patients using culture, PCR, immunological and biochemical tests. All these methods suffer from one or more limitations. Our lab has developed a quick PCR based detection of Neisseria meningitidis (bacterial meningitis) directly from the patient CSF samples using specific primers of virulent rmpM gene. The overall analysis completes in 80 min for confirmation of the disease. Amplicon of 308 bp of rmpM gene does not show homology with other organisms and can be used as a genetic marker for human bacterial meningitis caused by Neisseria meningitidis.